К вопросу о выражении контекcтyальной каузации (на материaле сложноподчиненных предложений с собcтвeнновмeщaющим значением) - Сабромене, Д. (Kalbotyra, 1990)
The object of the investigation is the ways of expressing causation in the complex sentence of the type “Oнa злила его тем, что внимательно и сосредоточенно и выполняла любую работу” (B. Шукшин). The rise of causative relations is promoted by lexical-syntactical coordination of the basic components of the complex sentence, lexical-grammatical nature of the key word and the presence of analytical unit “тем, что”.